Vulcanization type hydrogenation catalyst and preparation method thereof

By adding additives such as square amide during the preparation process of the sulfurized hydrogenation catalyst, the hydrogen bonding effect is used to weaken the force between the active component and the carrier, solving the problem that the catalyst is not easy to be completely sulfurized, and improving the sulfurization degree and processing capacity of the catalyst. Hydrogen activity simplifies the preparation process and reduces costs.

CN119327496AActive Publication Date: 2025-01-21CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310867540.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-15
Publication Date
2025-01-21
Estimated Expiration
2043-07-15

AI Technical Summary

Technical Problem

The preparation process of existing vulcanization hydrogenation catalysts is complex, with high total manufacturing cost, and strong force between active components and support, which makes the catalyst not easy to completely vulcanize, and the number of Class II active phase structures is small, which affects the hydrogenation activity.

Method used

By adding the first additive, such as squaramide, during the preparation process of the catalyst, its hydrogen bonding effect is used to weaken the force between the active component and the carrier, so that the sulfur-containing compound and the active metal can interact better, and the active metal component can be improved. Fully vulcanized and evenly distributed.

Benefits of technology

The sulfurization degree of the catalyst and the number of type II active phase structures are increased, the hydrogenation activity is enhanced, the preparation process is simplified, and the cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119327496A_ABST
    Figure CN119327496A_ABST
Patent Text Reader

Abstract

The invention discloses a sulfuration type hydrogenation catalyst and a preparation method thereof. The sulfuration type hydrogenation catalyst comprises a carrier, an active metal component and a first auxiliary agent, wherein the carrier is one or more of inorganic refractory oxides; the active metal comprises a VIB group metal and a VIII group metal, and the active metal component is distributed on the carrier in a sulfide form. The preparation method of the catalyst comprises the following steps: (1) preparing a solution containing active metal; (2) mixing the solution containing the active metal with a second auxiliary agent, introducing a vulcanizing agent and a first auxiliary agent, and uniformly mixing to obtain impregnation liquid; and (3) uniformly mixing the steeping liquor obtained in the step (2) with a carrier material, and then drying and roasting to obtain the sulfuration type hydrogenation catalyst. The preparation process and the pre-vulcanization process of the catalyst are organically combined, so that the active metal components are fully vulcanized, meanwhile, the active metal components are uniformly distributed on the carrier, and the hydrogenation activity of the catalyst is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of petrochemical catalysis, and relates to a hydrogenation catalytic material and a preparation method thereof, in particular to a sulfidation type hydrogenation catalyst and a preparation method thereof. Background Art

[0002] The active metals in the hydrogenation catalyst products currently available on the market are mainly in the form of metal oxides, and the oxidized catalysts usually need to be sulfurized to obtain better performance. Presulfurization of catalysts during hydrogenation is one of the important links in catalyst application. At present, the preparation of sulfurized catalysts generally includes three steps: carrier preparation, catalyst preparation, and catalyst presulfurization; there are problems such as complex catalyst preparation process and high total manufacturing cost. Moreover, each step of the catalyst preparation and sulfurization process will affect the quality of the final catalyst product.

[0003] The interaction between the active components and the carrier of the sulfided catalyst prepared by traditional sulfidation is strong, and the catalyst is not easy to be completely sulfided, resulting in a small number of type II active phase structures in the catalyst. Therefore, weakening the interaction between the active components and the carrier of the sulfided catalyst can increase the sulfidation degree of the catalyst, increase the number of type II active phase structures of the sulfided catalyst, and thus improve the hydrogenation activity of the sulfided hydrogenation catalyst.

[0004] CN103801334A discloses a method for preparing a sulfidation type hydrogenation catalyst, which comprises kneading a carrier precursor with elemental sulfur and an auxiliary agent, forming, drying, loading a hydrogenation active metal component, and then heat treating to obtain a sulfidation type hydrogenation catalyst. The method has a simple preparation process and low cost. However, the elemental sulfur and the hydrogenation active metal component are added step by step, and the elemental sulfur first reacts with the carrier material, and the interaction with the active metal component is affected, which is not conducive to the sulfidation reaction of the active metal component, thereby affecting the utilization rate of the active metal and the catalyst activity.

[0005] Combining the above analysis, it can be found that the development of new sulfurized catalyst preparation process has broad application prospects. Summary of the invention

[0006] In view of the problems and deficiencies in the prior art, the main purpose of the present invention is to provide a sulfurized hydrogenation catalyst and a preparation method thereof, organically combining the catalyst preparation and presulfidation process, weakening the interaction between the active component of the hydrogenation catalyst and the carrier through the hydrogen bonding effect of the first auxiliary agent, and making the sulfur-containing compound and the active metal interact better, so that the active metal component is fully sulfurized, while ensuring that the active metal component is evenly distributed on the carrier, thereby improving the hydrogenation activity of the catalyst. The addition of the auxiliary agent well solves the problem that the interaction between the active component of the sulfurized hydrogenation catalyst and the carrier is strong, the catalyst is not easy to be completely sulfurized, and the number of Class II active phase structures is small.

[0007] The first aspect of the present invention provides a sulfidation-type hydrogenation catalyst, which includes a carrier, an active metal component, a sulfiding agent, and a first auxiliary agent; wherein the carrier is one or more of inorganic refractory oxides; the active metal includes a VIB group metal and a VIII group metal, and the active metal component is distributed on the carrier in the form of a sulfide.

[0008] Preferably, in the above-mentioned sulfurized hydrogenation catalyst, as some specific embodiments, the first auxiliary agent is one or more of urea, thiourea, tert-butylthiourea, N-tert-butylurea, and squaramide, preferably squaramide. Based on the weight of the catalyst, the content of the first auxiliary agent is 2% to 10%, preferably 3% to 5%.

[0009] Preferably, in the above-mentioned sulfidation-type hydrogenation catalyst, as some specific embodiments, the first auxiliary agent forms a S...HN bond with sulfur S in the active metal sulfide by utilizing the NH bond contained therein, and forms a hydrogen bond with the hydroxyl group on the surface of the carrier.

[0010] Preferably, in the above-mentioned sulfided hydrogenation catalyst, as some specific embodiments, the VIB group metal is Mo and / or W, and the VIII group metal is Ni and / or Co.

[0011] Preferably, in the above-mentioned sulfidation-type hydrogenation catalyst, as some specific embodiments, the active metal is further preferably Mo and Ni.

[0012] Preferably, in the above-mentioned sulfidation-type hydrogenation catalyst, as some specific embodiments, the carrier is an inorganic refractory oxide, and the inorganic refractory oxide can be selected from at least one of alumina, silicon oxide, zirconium oxide, titanium oxide, silicon-containing alumina, and silicon-containing zirconium oxide, preferably alumina.

[0013] Preferably, in the above-mentioned sulfided hydrogenation catalyst, as some specific embodiments, based on the weight of the catalyst, the active metal component is 22% to 28% by element, preferably 23% to 26%; the sulfur content is 6% to 10%, preferably 7% to 8.5%. The content of the VIB group metal is 18% to 24% by element, and the content of the VIII group metal is 3% to 6% by element.

[0014] Preferably, in the above-mentioned sulfide-type hydrogenation catalyst, as some specific embodiments, the average stacking number of active phase (MoS2) lamellae is 2.7 to 4.6 layers, preferably 3.8 to 4.6 layers, and the average length of the active phase (MoS2) lamellae is 4.9 to 7.8 nm, preferably 5.3 to 6.8 nm.

[0015] Preferably, in the above-mentioned sulfided hydrogenation catalyst, as some specific embodiments, the mechanical strength of the catalyst is 230 to 250 N / cm.

[0016] Preferably, in the above-mentioned sulfided hydrogenation catalyst, as some specific embodiments, the specific surface area of ​​the catalyst is 240 to 380 m 2 / g, preferably 320 to 360 m 2 / g.

[0017] Preferably, in the above-mentioned sulfided hydrogenation catalyst, as some specific embodiments, the pore volume of the catalyst is 0.5 mL / g to 0.8 mL / g, preferably 0.7 mL / g to 0.8 mL / g.

[0018] A second aspect of the present invention provides a method for preparing a sulfided hydrogenation catalyst, comprising the following steps:

[0019] (1) preparing a solution containing active metals;

[0020] (2) mixing the active metal-containing solution with the second auxiliary agent, introducing a sulfiding agent and the first auxiliary agent and mixing them evenly to obtain an impregnation solution;

[0021] (3) The impregnation solution obtained in step (2) is mixed evenly with the carrier material, and then dried and calcined to obtain a sulfided hydrogenation catalyst.

[0022] Preferably, in the preparation method of the above-mentioned sulfidation-type hydrogenation catalyst, the solution containing active metals in step (1) can be prepared by any of the existing methods in the art, and those skilled in the art can make optional and appropriate adjustments according to actual needs. Specifically, the active metal-containing compound can be mixed with water and an optional P-containing compound, and the P-containing compound can be one or more of phosphoric acid, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate, preferably phosphoric acid; further, adding phosphoric acid and stirring under heating conditions can promote the dissolution of the active metal-containing compound in water, and the heating temperature is controlled to be 60°C to 95°C, preferably 80°C to 90°C. The concentration of the solution can be adjusted by the amount of each compound used, so as to prepare a catalyst with a required active component content, and the preparation method of the solution is well known to those skilled in the art.

[0023] Preferably, in the preparation method of the above-mentioned sulfided hydrogenation catalyst, the active metal in step (1) includes one or more of Group VIB metals and / or Group VIII metals; the compound containing the Group VIB metal may be one or more of molybdenum oxide, ammonium molybdate, tungsten oxide, and ammonium tungstate, preferably one or more of molybdenum oxide and ammonium molybdate; the compound containing the Group VIII metal may be one of basic nickel carbonate, basic cobalt carbonate, nickel oxide, and cobalt oxide, preferably one or more of basic nickel carbonate and nickel oxide.

[0024] Preferably, in the preparation method of the above-mentioned sulfided hydrogenation catalyst, the second auxiliary agent described in step (2) can be one or more of an alcohol solvent, a ketone solvent, and a nitrile solvent having a carbon number of 1 to 3, preferably an alcohol solvent; more specifically, one or more of ethanol, methanol, acetone, acetonitrile, ethylene glycol, n-propanol, and isopropanol, preferably one or more of ethanol, methanol, ethylene glycol, n-propanol, and isopropanol.

[0025] Preferably, in the method for preparing the above-mentioned sulfidation-type hydrogenation catalyst, the volume ratio of the solution containing the active metal to the second auxiliary agent is 1:1 to 4:1, preferably 1:1 to 2:1.

[0026] Preferably, in the preparation method of the above-mentioned sulfurized hydrogenation catalyst, the vulcanizing agent in step (2) can be one or more of sulfur powder or sulfur-containing compounds, and the sulfur-containing compound is one or more of carbon disulfide, dimethyl sulfoxide, and dimethyl disulfide. When the vulcanizing agent is sulfur powder, a vulcanization aid needs to be added, and the vulcanization aid can be kerosene or a mixture of kerosene and diesel, preferably a mixture of kerosene and diesel, and the volume ratio of kerosene to diesel can be 1:1 to 10:1, preferably 2:1 to 4:1.

[0027] Preferably, in the preparation method of the above-mentioned sulfurized hydrogenation catalyst, the first auxiliary agent in step (2) can be one or more of urea, thiourea, tert-butylthiourea, N-tert-butylurea, and squaramide, preferably squaramide.

[0028] Preferably, in the method for preparing the above-mentioned sulfided hydrogenation catalyst, the mixing in step (2) is carried out at 50°C to 75°C, preferably 60°C to 75°C.

[0029] Preferably, in the preparation method of the above-mentioned sulfide-type hydrogenation catalyst, the support material in step (3) is an inorganic refractory oxide, and the inorganic refractory oxide can be selected from at least one of aluminum oxide, silicon oxide, zirconium oxide, titanium oxide, silicon-containing aluminum oxide, and silicon-containing zirconium oxide, preferably aluminum oxide.

[0030] Preferably, in the method for preparing the above-mentioned sulfidation-type hydrogenation catalyst, the support material in step (3) is preferably a mixture of an inorganic refractory oxide powder (such as γ-alumina powder, etc.) and a molding aid, and the molding aid can be one or more of nitric acid, sesbania powder, silica sol, aluminum sol, and water. Furthermore, the inorganic refractory oxide powder is first calcined at a temperature of 450 to 600° C. for a calcination time of 1.5 to 2.5 hours.

[0031] Preferably, in the preparation method of the above-mentioned sulfide-type hydrogenation catalyst, after the impregnation liquid and the carrier material are evenly mixed in step (3), a molding aid is added for kneading and molding treatment. The molding aid can be one or more of nitric acid, sesbania powder, silica sol, aluminum sol, and water. The molding method can adopt any one of the existing molding methods in the art, such as extrusion.

[0032] Preferably, in the method for preparing the sulfided hydrogenation catalyst, the drying temperature in step (3) is 80° C. to 150° C., preferably 100° C. to 130° C. The drying time is 2 to 4 hours, preferably 2.5 to 3.5 hours.

[0033] Preferably, in the preparation method of the above-mentioned sulfided hydrogenation catalyst, the calcination temperature in step (3) is 350°C to 600°C, and the calcination time is 2 to 4 hours. Preferably, it includes two stages of calcination, wherein the first stage calcination temperature is 350°C to 450°C, preferably 380°C to 420°C; the calcination time is 1 to 2 hours, preferably 1.5 to 2 hours. The second stage calcination temperature is 450°C to 600°C, preferably 500°C to 550°C. The calcination time is 1 to 2 hours, preferably 1.5 to 2 hours.

[0034] Furthermore, in the method for preparing the above-mentioned sulfidation-type hydrogenation catalyst, the calcination in step (3) is carried out under an inert atmosphere, specifically, under a nitrogen or inert gas atmosphere.

[0035] The third aspect of the present invention provides a sulfided hydrogenation catalyst obtained by the above preparation method.

[0036] The fourth aspect of the present invention provides a process for hydrogenation treatment of hydrocarbon-containing compounds, wherein the hydrocarbon-containing compounds and hydrogen are introduced into a reactor, and the reactor is filled with the above-mentioned sulfidation type hydrogenation catalyst.

[0037] Furthermore, in the above-mentioned hydrocarbon-containing compound hydroprocessing process, the hydrocarbon-containing compound may be at least one of gasoline, diesel, and wax oil.

[0038] Furthermore, in the above-mentioned hydrocarbon compound hydrotreating process, the hydrogenation reaction conditions are generally as follows: reaction pressure of 3.0 to 10.0 MPa, reaction temperature of 300 to 420°C, liquid hourly volume space velocity of 1.0 to 2.0 h -1 , the volume ratio of hydrogen to oil is 300-800.

[0039] Compared with the existing methods, the sulfided hydrogenation catalyst and the preparation method thereof provided by the present invention have the following advantages:

[0040] (1) The novel integrated sulfidation type hydrogenation catalyst preparation method provided by the present invention can complete the catalyst preparation and catalyst sulfurization at one time, the catalyst preparation process is simple, the manufacturing cost of the sulfidation type catalyst is greatly reduced, the start-up time is shortened, and the use of toxic and harmful sulfiding agents is avoided, providing technical support for the safe and efficient production of enterprises. Especially when there are restrictions on the transportation of sulfiding agents, it is more practical to solve the problems of safe production and environmental protection of oil refining enterprises. At the same time, the sulfidation type hydrogenation catalyst obtained has a large pore volume and specific surface area, a high degree of sulfidation, a high dispersion of active metals, and the catalyst has a high hydrogenation activity.

[0041] (2) In the preparation method of the sulfidation type hydrogenation catalyst provided by the present invention, by adding an auxiliary agent, the NH bond contained in the auxiliary agent has a strong proton providing ability, and can form S...HN hydrogen bonds with sulfur in the active metal sulfide and hydrogen bonds with hydroxyl groups on the surface of the carrier, so as to coat the active metal sulfide, weaken the interaction between the active components of the hydrogenation catalyst and the carrier, effectively inhibit the growth and agglomeration of the active components, increase the degree of sulfidation of the catalyst, and then increase the number of active phase structures of the type II of the sulfidation type catalyst, and improve the hydrogenation activity of the sulfidation type hydrogenation catalyst. At the same time, the auxiliary agent has a large steric hindrance, which can better disperse the active metal and inhibit its growth and agglomeration.

[0042] (3) In the preparation method of the integrated sulfidation type hydrogenation catalyst provided by the present invention, the problem of the difficulty of the active metal and the sulfiding agent to be miscible is solved by adding an organic solvent and a suitable heating temperature. By selecting a suitable organic solvent and a suitable treatment temperature and at a specific ratio of the active metal solution to the organic solvent, the active metal and the sulfiding agent can be fully mixed to form a uniform and stable solution, thus solving the problem of the difficulty of the active metal and the sulfiding agent to be miscible.

[0043] (4) In the preparation method of the integrated sulfidation hydrogenation catalyst provided by the present invention, since the drying and calcination unit of the new integrated sulfidation catalyst is quite different from that of the conventional oxidized catalyst, the influence of the heat treatment process on the mechanical strength of the catalyst is a difficult problem that must be solved. Through investigation of different treatment conditions, it is found that the mechanical strength of the catalyst is improved after being dried and then calcined. The reason may be that after drying to remove excess moisture and cooling to room temperature, the surface of the catalyst strip shrinks. During the process of heating to the calcination temperature again, the stress inside the catalyst is reduced, which increases the mechanical strength of the finished product, and a better mechanical strength can be obtained to meet the use requirements of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 This is the AHRTEM image of the catalyst prepared in Example 1 of the present invention.

[0045] Figure 2This is the AHRTEM image of the catalyst prepared in Comparative Example 1 of the present invention.

[0046] Figure 3 The SEM-EDS analysis results of catalyst A. DETAILED DESCRIPTION

[0047] The novel integrated sulfidation hydrogenation catalyst and the preparation method thereof involved in the present invention are further described in detail below through examples and comparative examples to help readers better understand the present invention, but do not constitute any limitation on the scope of the present invention.

[0048] The experimental methods in the following examples, unless otherwise specified, are all conventional methods in the art. The experimental materials used in the following examples, unless otherwise specified, were purchased from conventional biochemical reagent stores.

[0049] The analysis method of the present invention: the specific surface area and the pore volume are measured by a low-temperature liquid nitrogen physical adsorption method.

[0050] The test of the active phase of the present invention is analyzed by transmission electron microscopy (TEM) to obtain the microscopic appearance of the active metal active phase. The average number of stacked layers and the average lamella length of the molybdenum disulfide wafers in the 20 randomly selected TEM photos of each sample are counted by Digital Micrograph software to calculate the distribution of the active phase on the carrier surface. The calculation formulas for the average lamella length and the average number of stacked layers are as follows:

[0051] L=∑S i L i / ∑S i

[0052]

[0053] Where S i The length of the slice is L i The number of layers, L is in nm; X i For N i In this article, the degree of sulfidation of the catalyst is the percentage of sulfur consumed in actual sulfidation to the theoretically calculated sulfur required for complete sulfidation.

[0054] In this paper, the lateral compression strength is measured using a strength meter using the Q / SH 361 926-2020 method.

[0055] In this paper, SEM-EDS technology uses scanning electron microscope technology and energy spectrometer to achieve accurate analysis of samples. It directly observes the sample surface through scanning electron microscope and uses energy spectrometer to analyze the composition of the sample surface, so as to obtain the element distribution image and corresponding analysis data of the sample surface. The scanning electron microscope instrument model is Nova NanoSEM450, and the energy spectrometer instrument model is AZtec X-MaxN80.

[0056] Example 1

[0057] 70g of γ-alumina powder was roasted in a muffle furnace for 2 hours at a roasting temperature of 600°C, followed by the addition of 35g of SB powder and 5g of sesbania powder, and the mixture was uniformly mixed to obtain a solid material. Subsequently, 44.9g of molybdenum trioxide was mixed with 16.5g of basic nickel carbonate, 95mL of clean water was added thereto, heated and stirred at 90°C, and 3.1g of phosphoric acid was gradually added, and finally until the solution became clear and transparent, the molybdenum nickel phosphorus solution was filtered. 19.5g of dimethyl sulfoxide was added to 35mL of anhydrous ethanol and stirred thoroughly, and then 3g of square amide was added, followed by the addition of molybdenum nickel phosphorus solution, and stirred thoroughly at 70°C until the solution became uniform and transparent. Subsequently, 5.4g of nitric acid was added thereto, and after being fully mixed, it was added to the previously uniformly mixed solid material and mixed thoroughly. After kneading and extruding, it was dried at 120°C for 3h under nitrogen conditions, and then roasted at 400°C for 2h and 500°C for 1.5h under nitrogen conditions to obtain catalyst A.

[0058] Example 2

[0059] 70g of silicon-containing alumina powder was roasted in a muffle furnace for 2.5 hours at a roasting temperature of 550°C, followed by the addition of 35g of SB powder and 5g of sesbania powder, and the mixture was uniformly mixed to obtain a solid material. Subsequently, 44.9g of molybdenum trioxide was mixed with 7.5g of nickel oxide, 88mL of clean water was added thereto, heated and stirred at 90°C, and 3.1g of phosphoric acid was gradually added thereto, and finally until the solution became clear and transparent, filtration was started to obtain a molybdenum nickel phosphorus solution. 12g of dimethyl disulfide was added to 40mL of isopropanol and stirred thoroughly, and then 3.5g of N-tert-butyl urea was added, followed by the addition of molybdenum nickel phosphorus solution, stirred thoroughly at 65°C until the solution became uniform and transparent, and the solution was added to the previously uniformly mixed solid material, and then 5.4g of nitric acid was added thereto, and after kneading and extruding, it was dried at 110°C under nitrogen for 2.5h, and then roasted at 420°C for 1.5h and 500°C for 2h under nitrogen to obtain catalyst B.

[0060] Example 3

[0061] 70g of γ-alumina powder was roasted in a muffle furnace for 2 hours at a roasting temperature of 500°C, and then 5g of sesbania powder was added and mixed evenly to obtain a solid material. Subsequently, 60.0g of ammonium molybdate was mixed with 7.5g of nickel oxide, 90ml of clean water was added thereto, heated and stirred at 90°C, and 3.1g of phosphoric acid was gradually added, and finally until the solution became clear and transparent, began to filter to obtain a molybdenum nickel phosphorus solution. 9.5g of carbon disulfide was added to 35ml of ethylene glycol and stirred thoroughly, and then 4g of tert-butyl thiourea was added, followed by the molybdenum nickel phosphorus solution, stirred thoroughly at 75°C until the solution became uniform and transparent, and the solution was added to the previously mixed solid material, and finally 68.0g of aluminum sol was added thereto and mixed thoroughly. After kneading and extruding, it was dried at 130°C for 3h under nitrogen conditions, and then roasted at 360°C for 1.5h and 580°C for 2h under nitrogen conditions to obtain catalyst C.

[0062] Example 4

[0063] 70g of γ-alumina powder was roasted in a muffle furnace for 2.5 hours at a roasting temperature of 450°C, followed by the addition of 35g of SB powder and 5g of sesbania powder, and the mixture was uniformly mixed to obtain a solid material. Subsequently, 44.9g of molybdenum trioxide was mixed with 16.5g of basic nickel carbonate, 95mL of clean water was added thereto, heated and stirred at 90°C, and 3.1g of phosphoric acid was gradually added thereto, and finally until the solution became clear and transparent, it was filtered to obtain a molybdenum nickel phosphorus solution. 12g of dimethyl disulfide was added to 40mL of isopropanol and stirred thoroughly, and then 3g of square amide was added, followed by the addition of molybdenum nickel phosphorus solution, and stirred thoroughly at 70°C until the solution became uniform and transparent. Subsequently, 5.4g of nitric acid was added thereto, mixed thoroughly, and then added to the previously mixed solid material and mixed thoroughly. After kneading and extruding, it was dried at 140°C for 2h under nitrogen conditions, and then roasted at 500°C for 3h under nitrogen conditions to obtain catalyst D.

[0064] Example 5

[0065] 70g of γ-alumina powder was roasted in a muffle furnace for 2 hours at a roasting temperature of 600°C, followed by the addition of 35g of SB powder and 5g of sesbania powder, and the mixture was uniformly mixed to obtain a solid material. Subsequently, 44.9g of molybdenum trioxide was mixed with 16.5g of basic nickel carbonate, 95mL of clean water was added thereto, heated and stirred at 90°C, and 3.1g of phosphoric acid was gradually added thereto, and finally until the solution became clear and transparent, filtration was started to obtain a molybdenum nickel phosphorus solution. 12g of dimethyl disulfide was added to 35ml of ethylene glycol and stirred thoroughly, and then 3g of square amide was added, followed by the addition of molybdenum nickel phosphorus solution, and stirred thoroughly at 70°C until the solution became uniform and transparent. Subsequently, 5.4g of nitric acid was added thereto, and after being fully mixed, it was added to the previously mixed solid material and mixed thoroughly. After kneading and extruding, it was dried at 90°C for 4h under nitrogen conditions, and then roasted at 450°C for 1h and 580°C for 1.5h under nitrogen conditions to obtain catalyst E.

[0066] Comparative Example 1

[0067] 70g of γ-alumina powder was roasted in a muffle furnace for 2 hours at a roasting temperature of 600°C, followed by the addition of 35g of SB powder and 5g of sesbania powder, and the mixture was uniformly mixed to obtain a solid material. Subsequently, 44.9g of molybdenum trioxide was mixed with 16.5g of basic nickel carbonate, 95ml of clean water was added thereto, heated and stirred at 90°C, and 3.1g of phosphoric acid was gradually added thereto, and finally, the solution became clear and transparent and began to be filtered to obtain a molybdenum nickel phosphorus solution. 19.5g of dimethyl sulfoxide was added to the molybdenum nickel phosphorus solution and stirred thoroughly, and then 3g of square amide was added and stirred thoroughly at 70°C. Subsequently, 5.4g of nitric acid was added thereto, mixed thoroughly, and then added to the previously uniformly mixed solid material and mixed thoroughly. After kneading and extruding, the strips were dried at 120°C for 3h under nitrogen conditions, and then roasted at 400°C for 2h and 500°C for 1.5h under nitrogen conditions to obtain catalyst F.

[0068] Comparative Example 2

[0069] 70g of γ-alumina powder was roasted in a muffle furnace for 2 hours at a roasting temperature of 600°C, followed by the addition of 35g of SB powder and 5g of sesbania powder, and the mixture was uniformly mixed to obtain a solid material. Subsequently, 44.9g of molybdenum trioxide was mixed with 16.5g of basic nickel carbonate, 95ml of clean water was added thereto, heated and stirred at 90°C, and 3.1g of phosphoric acid was gradually added thereto, and finally until the solution became clear and transparent, filtration was started to obtain a molybdenum nickel phosphorus solution. 19.5g of dimethyl sulfoxide was added to 35mL of anhydrous ethanol and stirred thoroughly, followed by the addition of molybdenum nickel phosphorus solution, and stirred thoroughly at 70°C until the solution became uniform and transparent. Subsequently, 5.4g of nitric acid was added thereto, mixed thoroughly, and then added to the previously uniformly mixed solid material and mixed thoroughly. After kneading and extruding, the mixture was dried at 120°C for 3h under nitrogen conditions, and then roasted at 400°C for 2h and 500°C for 1.5h under nitrogen conditions to obtain catalyst G.

[0070] Comparative Example 3

[0071] 70g of γ-alumina powder was roasted in a muffle furnace for 2 hours at a roasting temperature of 600°C, followed by the addition of 35g of SB powder and 5g of sesbania powder, and the mixture was uniformly mixed to obtain a solid material. Subsequently, 44.9g of molybdenum trioxide was mixed with 16.5g of basic nickel carbonate, 95ml of clean water was added thereto, heated and stirred at 90°C, and 3.1g of phosphoric acid was gradually added thereto, and finally, until the solution became clear and transparent, filtration was started to obtain a molybdenum nickel phosphorus solution. 19.5g of dimethyl sulfoxide was added to the molybdenum nickel phosphorus solution, stirred thoroughly at 70°C, and then 5.4g of nitric acid was added thereto, mixed thoroughly, and then added to the previously mixed solid material and mixed thoroughly. After kneading and extruding, the mixture was dried at 120°C for 3h under nitrogen conditions, and then roasted at 400°C for 2h and 500°C for 1.5h under nitrogen conditions to obtain catalyst H.

[0072] Table 1 Catalyst sample property parameters

[0073]

[0074]

[0075] Table 1 shows the average stacking number of active phase flakes and the average length of active phase flakes in the catalyst obtained by statistics. The statistical results show that Examples 1-5 all have a higher number of stacking layers and a shorter average length, indicating that the active components are evenly distributed on the carrier and have more metal active sites; while the number of stacking layers of Comparative Examples 1 and 2 is lower than that of the five embodiments, and the average length is also higher than that of the five embodiments, indicating that the dispersibility of the active components is lower than that of the five embodiments. The number of stacking layers of Comparative Example 3 is lower than that of Comparative Examples 1 and 2, and the average length is higher than that of Comparative Examples 1 and 2, indicating that the dispersibility of the active components is lower than that of Comparative Examples 1 and 2. The increase in the number of stacking layers can generate highly active type II active phases on the one hand, improving the hydrogenation activity of the catalyst, but on the other hand, MoS2 flakes are prone to agglomeration, resulting in a decrease in the dispersion of active metal components. Therefore, an appropriate number of stacking layers and a slightly shorter average length are beneficial to improving the hydrogenation activity of the catalyst. It is generally believed that the metal stacking is best at about 3 to 5 layers.

[0076] Evaluation test:

[0077] The catalyst samples prepared in the examples and comparative examples were evaluated for activity by a microreactor. The properties of the raw oil used for the evaluation are shown in Table 2. The microreactor evaluation temperature was 350°C, the pressure was 3.4 MPa, the hydrogen-to-oil volume ratio was 500, and the volume space velocity was 1.5 h -1 The catalyst activity evaluation results are shown in Table 3.

[0078] Table 2 Main properties of crude oil

[0079]

[0080]

[0081] Table 3 Catalyst evaluation results

[0082] catalyst <![CDATA[Sulfur, μg.g -1 > <![CDATA[Nitrogen, μg.g -1 > A 23.5 <1.0 B 24.7 <1.0 C 27.1 <1.0 D 27.6 <1.0 E 25.1 <1.0 F 71.2 5.8 G 67.4 5.3 H 123.7 9.6

[0083] It can be seen from the catalyst evaluation results that the new integrated sulfidation hydrogenation catalyst has a very high hydrodesulfurization and denitrification activity.

[0084] Table 4 Catalyst sulfidation results

[0085]

[0086]

[0087] It can be seen from Table 4 that catalyst AE has a very high degree of sulfidation and the active components are fully utilized, while catalyst FH has a relatively low degree of sulfidation and the active components cannot be fully utilized.

[0088] Figure 3 The SEM-EDS analysis results of the sulfided catalyst A are shown in Figure 2. Figure 3 It can be seen that the distribution of active metals and sulfur elements at each point of the cross section of catalyst A is relatively uniform, indicating that this method is beneficial to improving the dispersion of metals and sulfur. The distribution of active metal components on the carrier surface can be significantly improved, and the number of active phases per unit catalyst surface can be increased, which can improve the hydrogenation activity of the catalyst.

Claims

1. A sulfidation type hydrogenation catalyst, comprising a carrier, an active metal component, and a first additive; wherein the carrier is one or more of inorganic refractory oxides; the active metal comprises a VIB group metal and a VIII group metal, and the active metal component is distributed on the carrier in the form of a sulfide; and the first additive is one or more of urea, thiourea, tert-butylthiourea, N-tert-butylurea, and squaramide.

2. The sulfided hydrogenation catalyst according to claim 1, wherein The first auxiliary agent is squaramide.

3. The sulfided hydrogenation catalyst according to claim 1, wherein The first auxiliary agent forms S...HN bonds with sulfur S in the active metal sulfide by utilizing the NH bonds contained therein, and forms hydrogen bonds with the hydroxyl groups on the surface of the carrier.

4. The sulfided hydrogenation catalyst according to claim 1, wherein The metals of Group VIB are Mo and / or W, and the metals of Group VIII are Ni and / or Co.

5. The sulfided hydrogenation catalyst according to claim 1, wherein The active metals are Mo and Ni.

6. The sulfided hydrogenation catalyst according to claim 1, wherein The inorganic refractory oxide may be selected from at least one of alumina, silicon oxide, zirconium oxide, titanium oxide, silicon-containing alumina, and silicon-containing zirconium oxide, preferably alumina.

7. The sulfided hydrogenation catalyst according to claim 1, wherein The average stacking number of active phase crystals is 2.7 to 4.6 layers, preferably 3.8 to 4.6 layers, and the average length of active phase crystals is 4.9 to 7.8 nm, preferably 5.3 to 6.8 nm.

8. The sulfided hydrogenation catalyst according to claim 1, wherein The specific surface area of ​​the catalyst is 240-380 m 2 / g, preferably 320 to 360 m 2 / ; the pore volume is 0.5mL / g to 0.8mL / g, preferably 0.7mL / g to 0.8mL / g; the mechanical strength of the catalyst is 230 to 250N / cm.

9. The sulfided hydrogenation catalyst according to claim 1, wherein Based on the weight of the catalyst, the active metal component content is 22% to 28%, preferably 23% to 26%; the sulfur content is 6% to 10%, preferably 7% to 8.5%; the VIB group metal content is 18% to 24%, and the VIII group metal content is 3% to 6%.

10. The sulfided hydrogenation catalyst according to claim 1, wherein Based on the weight of the catalyst, the content of the first auxiliary agent is 2% to 10%, preferably 3% to 5%.

11. A method for preparing a sulfidation type hydrogenation catalyst, comprising the following steps: (1) preparing a solution containing active metals; (2) mixing the solution containing the active metal with the second auxiliary agent, introducing a vulcanizing agent and the first auxiliary agent and mixing them evenly to obtain an impregnation solution; the first auxiliary agent may be one or more of urea, thiourea, tert-butylthiourea, N-tert-butylurea, and squaramide; the second auxiliary agent may be one or more of an alcohol solvent having 1 to 3 carbon atoms, a ketone solvent, and a nitrile solvent; (3) The impregnation solution obtained in step (2) is mixed evenly with the carrier material, and then dried and calcined to obtain a sulfided hydrogenation catalyst.

12. The method for preparing a sulfided hydrogenation catalyst according to claim 11, wherein: In step (1), a solution containing active metals is prepared by mixing a compound containing active metals with water and an optional P-containing compound, wherein the active metals include one or more of Group VIB metals and / or Group VIII metals; and the P-containing compound is one or more of phosphoric acid, diammonium phosphate, and diammonium hydrogen phosphate, preferably phosphoric acid.

13. The method for preparing a sulfided hydrogenation catalyst according to claim 12, wherein: The compound containing the metal of Group VIB is one or more of molybdenum oxide, ammonium molybdate, tungsten oxide, and ammonium tungstate, preferably one or more of molybdenum oxide and ammonium molybdate; the compound containing the metal of Group VIII is one of basic nickel carbonate, basic cobalt carbonate, nickel oxide, and cobalt oxide, preferably one or more of basic nickel carbonate and nickel oxide.

14. The method for preparing a sulfided hydrogenation catalyst according to claim 11, wherein: The second auxiliary agent described in step (2) is one or more of ethanol, methanol, acetone, acetonitrile, ethylene glycol, n-propanol, and isopropanol, preferably one or more of ethanol, methanol, ethylene glycol, n-propanol, and isopropanol.

15. The method for preparing a sulfided hydrogenation catalyst according to claim 11, wherein: The volume ratio of the solution containing active metal to the second auxiliary agent is 1:1 to 4:1, preferably 1:1 to 2:

1.

16. The method for preparing a sulfided hydrogenation catalyst according to claim 11, wherein: The vulcanizing agent in step (2) is one or more of sulfur powder or sulfur-containing compounds, and the sulfur-containing compound is one or more of carbon disulfide, dimethyl sulfoxide, and dimethyl disulfide.

17. The method for preparing a sulfided hydrogenation catalyst according to claim 11, wherein: The mixing in step (2) is carried out at 50°C to 75°C, preferably 60°C to 75°C.

18. The method for preparing a sulfided hydrogenation catalyst according to claim 11, wherein: The carrier material in step (3) is an inorganic refractory oxide, which is selected from at least one of alumina, silicon oxide, zirconium oxide, titanium oxide, silicon-containing alumina, and silicon-containing zirconium oxide, preferably alumina.

19. The method for preparing a sulfided hydrogenation catalyst according to claim 11, wherein: The carrier material in step (3) is a mixture of an inorganic refractory oxide powder and a molding aid, wherein the molding aid is one or more of nitric acid, sesbania powder, silica sol, aluminum sol, and water; the inorganic refractory oxide powder is first calcined at a temperature of 450 to 600° C. for a time of 1.5 to 2.5 hours.

20. The method for preparing a sulfided hydrogenation catalyst according to claim 11, wherein: In step (3), the impregnation liquid and the carrier material are evenly mixed, and then a molding aid is added to perform kneading and molding treatment. The molding aid is one or more of nitric acid, sesbania powder, silica sol, aluminum sol, and water.

21. The method for preparing a sulfided hydrogenation catalyst according to claim 11, wherein: The drying temperature in step (3) is 80°C to 150°C, preferably 100°C to 130°C; the drying time is 2 to 4 hours, preferably 2.5 to 3.5 hours.

22. The method for preparing a sulfided hydrogenation catalyst according to claim 11, wherein: The calcination temperature in step (3) is 350°C to 600°C, and preferably includes two stages of calcination, wherein the calcination temperature of the first stage is 350°C to 450°C, preferably 380°C to 420°C; and the calcination temperature of the second stage is 450°C to 600°C, preferably 500°C to 550°C.

23. A process for hydrogenating hydrocarbon compounds, comprising introducing hydrocarbon compounds and hydrogen into a reactor, wherein the reactor is filled with a sulfided hydrogenation catalyst according to any one of claims 1 to 10 and / or a sulfided hydrogenation catalyst obtained by the preparation method according to any one of claims 11 to 22.

Citation Information

Patent Citations

  • Preparation method of sulfuration-type hydrogenation catalyst

    CN103801334A

  • Preparation method for vulcanization type hydrogenation catalyst

    CN102836736A

  • Vulcanization type hydrogenation catalyst, preparation method and applications thereof

    CN107971034A

  • Vulcanization type hydrogenation catalyst and preparation method and application thereof

    CN109569662A

  • Hydrogenation catalyst composition and its prepn. method

    CN1861259A